Optimization of Wireless Communication Coverage in Underground Tunnels Based on Zone Division - Yu Huo; Qingsong Hu; Yanjing Sun; Xiwang Guo; Liang Qi; Xiaohu Zhao; Enjie Ding (International Journal of Antennas and Propagation)
In order to reduce the path loss of the wireless communication signal in the underground tunnel, a scheme for configuring the antenna polarization of wireless systems based on a zone-division method is proposed. A multimodal method is used to estimate the effect of antenna polarization on the wireless propagation. When the optimal polarization of the antenna leading to low path loss is different in the zones near and far from the transmitting antenna, a dividing point is used to separate the zones. Experiments are conducted in an underground mine. It shows that the results by the multimodal method are consistent with the real data. Compared with the existing coverage schemes, the proposed scheme can obtain better coverage. Meanwhile, zone division has an important influence on the optimized performance of the wireless coverage. The zones divided based on Fresnel zone clearance and system identification are too small or too large, which result in incorrect polarization switching and high path loss.